Debt Sustainability Analyses for Italy, Spain and Portugal: Assessment and Recommendations - Jürgen Matthes (Intereconomics, 2018)
Despite the broad upswing in the euro area, it cannot be precluded that high public debts in some countries could spiral out of control if interest rates increase again. To analyse the relevance of this danger, a debt sustainability analysis is carried out using a narrow range of relatively realistic assumptions through 2022. While public debts will remain high for an extended period, reasonable fiscal primary surpluses will be sufficient to stabilise debt ratios, even if a moderate recession occurs.
Keywords: 330